miR-137 regulates PTP61F, affecting insulin signaling, metabolic homeostasis, and starvation resistance in Drosophila melanogaster - Saedi, Hana Ibrahim, author; Tsunoda, Susan, advisor; Hoerndli, Frederic, committee member; Amberg, Gregory, committee member; Di Pietro, Santiago, committee member (Colorado State University. Libraries, 2023)
miR-137 is a highly conserved brain-enriched microRNA (miRNA) that has been associated with neuronal function and proliferation. Here, we show that Drosophila miR-137 null mutants display increased body weight with enhanced triglyceride and glucose levels and decreased locomotor activity. When challenged by nutrient deprivation, miR-137 mutants exhibit reduced motivation to feed and significantly prolonged survival. Together, these phenotypes suggest a new role for miR-137 in energy homeostasis. Genetic epistasis experiments show that the starvation resistance of miR-137 mutants involves the insulin signaling pathway, and that loss of miR-137 results in drastically reduced phosphorylation/activation of the single insulin receptor, InR, in Drosophila. We explore the possibility that the protein tyrosine phosphatase61F (PTP61F), ortholog of TC-PTP/PTP1B, known to dephosphorylate InR across species, is a potential in vivo target of miR-137. We show that loss of miR-137 results in upregulation of an endogenously tagged PTP61F protein, and that genetically increasing levels of PTP61F mimics the loss of phosphorylated InR and increased starvation resistance seen in miR-137 mutants. Finally, we show that the enhanced starvation resistance of miR-137 mutants is normalized by activation of the insulin signaling pathway in the nervous system. Our study introduces miR-137 as a new player in the regulation of central insulin signaling and metabolic homeostasis.
Keywords: insulin signaling; miR-137; starvation resistance; metabolic homeostasis; Drosophila melanogaster; PTP61F